Problems of domestic practice of us of a method of financial factors (Путеводитель предпринимателя)
The perspective of prospects of use of a method of financial factors is considered by the domestic enterprises. Locates that the wide circulation of a method is limited to imperfection of standard and information base of calculation of factors of separate groups (in particular, liquidities, solvency and capital structures), plurality of approaches to definition of structure of articles of the financial and economic reporting of the enterprise on the basis of which they pay off, and lack of uniformity of regulatory base of determination of their threshold values. Recommendations and conclusions about necessary correction of settlement base of a method of financial factors for conditions used by the Russian enterprises of systems of the financial account and the reporting are provided.